"We are a family firm": An exploration of the motives for communicating the family business brand. Issue 1 (21st November 2017) - Binz Astrachan, Claudia; Botero, Isabel C.
Abstract : Purpose: Evidence suggests that some stakeholders perceive family firms as more trustworthy, responsible, and customer-oriented than public companies. To capitalize on these positive perceptions, owning families can use references about their family nature in their organizational branding and marketing efforts. However, not all family firms actively communicate their family business brand. With this in mind, the purpose of this paper is to investigate why family firms decide to promote their "family business brand" in their communication efforts toward different stakeholders. Design/methodology/approach: Data for this study were collected using an in-depth interview approach from 11 Swiss and German family business owners. Interviews were transcribed and coded to identify different themes that help explain the different motives and constraints that drive their decisions to promote the "family business brand." Findings: The analyses indicate that promoting family associations in branding efforts is driven by both identity-related (i.e. pride, identification) and outcome-related (e.g. reputational advantages) motives. However, there are several constraints that may negatively affect the promotion of the family business brand in corporate communication efforts. Originality/value: This paper is one of the first to explore why family businesses decide to communicate their "family business brand." Building on the findings, the authors present a conceptual framework identifying the antecedents and possible consequences of promoting a family firm brand. This framework can help researchers and practitioners better understand how the family business nature of the brand can influence decisions about the company's branding and marketing practices.